BrachyView: Proof‐of‐principle of a novel in‐body gamma camera for low dose‐rate prostate brachytherapy. Issue 4 (15th March 2013) - Petasecca, M.; Loo, K. J.; Safavi‐Naeini, M.; Han, Z.; Metcalfe, P. E.; Meikle, S.; Pospisil, S.; Jakubek, J.; Bucci, J. A.; Zaider, M.; Lerch, M. L. F.; Qi, Y.; et al.
Abstract : Purpose: : The conformity of the achieved dose distribution to the treatment plan strongly correlates with the accuracy of seed implantation in a prostate brachytherapy treatment procedure. Incorrect seed placement leads to both short and long term complications, including urethral and rectal toxicity. The authors present Brachy View, a novel concept of a fast intraoperative treatment planning system, to provide real‐time seed placement information based on in‐body gamma camera data. Brachy View combines the high spatial resolution of a pixellated silicon detector (Medipix2) with the volumetric information acquired by a transrectal ultrasound (TRUS). The two systems will be embedded in the same probe so as to provide anatomically correct seed positions for intraoperative planning and postimplant dosimetry. Dosimetric calculations are based on the TG‐43 method using the real position of the seeds. The purpose of this paper is to demonstrate the feasibility of Brachy View using the Medipix2 pixel detector and a pinhole collimator to reconstruct the real‐time 3D position of low dose‐rate brachytherapy seeds in a phantom. Methods: : Brachy View incorporates three Medipix2 detectors coupled to a multipinhole collimator. Three‐dimensionally triangulated seed positions from multiple planar images are used to determine the seed placement in a PMMA prostate phantom in real time.MATLAB codes were used to test the reconstruction method and to optimize the device geometry. Results: : The results presented in this paper show a 3D position reconstruction accuracy of the seed in the range of 0.5–3 mm for a 10–60 mm seed‐to‐detector distance interval ( Z direction), respectively. The Brachy View system also demonstrates a spatial resolution of 0.25 mm in the XY plane for sources at 10 mm distance from Medipix2 detector plane, comparable to the theoretical value calculated for an equivalent gamma camera arrangement. The authors successfully demonstrated the capability of Brachy View for real‐time imaging (using a 3 s data acquisition time) of different brachytherapy seed configurations (with an activity of 0.05 U) throughout a 60 × 60 × 60 mm 3 Perspex prostate phantom. Conclusions: : The newly developed miniature gamma camera component of Brachy View, with its high spatial resolution and real time capability, allows accurate 3D localization of seeds in a prostate phantom. Combination of the gamma camera with TRUS in a single probe will complete the Brachy View system.